Photosynthetic bacteria as an alternative wastewater treatment in freshwater aquarium fish set up - Wan Zabidii Wan Morni,; Mohd Fakhrul Hazim Hilmi Azman,; Nurul Ashikin Ismail,; Tan, Toh Hii; Sui, Sien Leong; Juriah Kamaludeen,; Suhaili Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Waste produced from aquaculture ultimately hampered the water quality and growth performance of species cultured. Therefore, the potential exploitation of photosynthetic bacteria (PSB) from aquaculture waste was investigated to treat the wastewater in the fish culture. In this study, the wastewater was collected from a fishpond and cultured in sunlight-exposed sterile bottles for 14 days. In the water additive experiment, five treatments (in a 30 cm3 aquarium) were prepared namely cultured PSB (T1), aquatic plant hornwort (T2), aquatic plant salvinia (T3), positive control (P), and negative control (N). Five individuals of Hyphessobrycon herbertaxelrodi (2.5±0.5 cm length) were placed in each treatment and reared for 30 days. Meanwhile, for the wastewater treatment, four treatments (in a 30 cm3 aquarium) were prepared namely wastewater from the hatchery fishpond (S1), wastewater from the hatchery fish tank (S2), positive control (P), and negative control (N). The results obtained indicate that T1 treatment significantly improved and maintained the water quality as compared to other treatments. The results showed the amount of ammonia and nitrite in S1 and S2 supplied with T1 for 30 days gradually decreased from day 1 until day 18. While zero amount of ammonia and nitrate was acquired from day 21 until day 30 of the wastewater experiment. The treatment with PSB showcased the bacteria's ability to utilize and absorb nutrients, thereby maintaining and improving water quality. The potential use of beneficial bacteria in the culture system can accelerate the nitrogen cycle for a sustainable way of wastewater management.